IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH THE APPLICATION OF LANGUAGE EXPERIENCE APPROACH - Eka Surya Fitriani; Yunita Agnes Sianipar (Universitas Negeri Medan, 2012)
This paper discusses improving students’ achievement in reading comprehension through the application of language experience approach. This paper will answer the question “Does the application of Language Experience Approach improve the students’ achievement in reading comprehension?” The objective of the study is aimed at finding out whether the application of Language Experience Approach improves the students’ achievement in reading comprehension. The sample of the research was the second grade students of SMA Panca Budi Medan, class XI – 2 science which consisted of 39 students, 19 boys and 20 girls. The technique of collecting data was by using three tests with two cycles in action research. The result showed that the application of language experience approach improved the students’ achievement in reading comprehension. Key Words: Reading Comprehension, Language Experience Approach